2011
DOI: 10.1134/s0021364011130066
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of the classical Bose-Einstein condensation of magnons in solid antiferromagnets

Abstract: International audienceResults of experiments in which the Bose-Einstein condensate of magnons is created in the CsMnF3 easy-plane antiferromagnet in a system with coupled nuclear-electron precession with dynamical frequency shift are presented. This condensate is similar to the Bose-Einstein condensate of magnons in superfluid 3He-A in aerogel

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 13 publications
3
15
0
1
Order By: Relevance
“…In [20], it was shown that the dynamical properties of the magnetic resonance in some antiferromagnets are similar to those of 3 He-A. Later BEC of nuclear magnons with k = 0, but quite different physical properties than nuclear magnons in 3 He, was experimentally observed in the easy-plane antiferromagnets CsMnF 3 and MnCO 3 at liquid helium temperature T = 1.5 K [21,22]. In this work, we focus theoretically on nontrivial conditions of BEC of nuclear magnons in the easy-plane antiferromagnets.…”
mentioning
confidence: 92%
“…In [20], it was shown that the dynamical properties of the magnetic resonance in some antiferromagnets are similar to those of 3 He-A. Later BEC of nuclear magnons with k = 0, but quite different physical properties than nuclear magnons in 3 He, was experimentally observed in the easy-plane antiferromagnets CsMnF 3 and MnCO 3 at liquid helium temperature T = 1.5 K [21,22]. In this work, we focus theoretically on nontrivial conditions of BEC of nuclear magnons in the easy-plane antiferromagnets.…”
mentioning
confidence: 92%
“…Within the framework of the Holstein–Primakov paradigm, a magnon gas is considered, which has all the properties of a Bose gas. In a number of works with solid-state magnets, such as CsMnF 27 and MnCO 28 , similar quantum effects of magnonic superfluidity were observed. In these antiferromagnets, coupled nuclear-electron precession is observed.…”
Section: Magnonic Becmentioning
confidence: 63%
“…The essence of this process is described in detail in the articles [25,26]. After a superfluif 3 He the mBEC and spin superflow were observed in antiferromagnets with coupled nuclearelectron precession CsMnF 3 [27] and MnCO 3 [28,29], where the positive frequency shift from the magnon density takes place.…”
Section: Theoretical Backgroundmentioning
confidence: 99%